Beyond the drug war: violence, forced displacement, and shale gas in northeastern Mexico (2000-2020) - Nieto, Raúl Iglesias (Crime, law and social change, 2024)
This article presents the results of an investigation about forced displacement in Mexico’s northeastern region - bordering the United States - where many municipalities have been affected by violence and depopulation in the past two decades (2000-2020), in the context of a so-called "drug war." From a critical perspective, the study is based on a quantitative methodology using spatial and statistical analysis to try to link forced displacement - caused by criminal violence - and the presence of important hydrocarbon deposits in the region. The main finding is that the most affected municipalities by violence are located precisely in the Burgos Basin area, which has the largest shale gas reserves in the country. The evidence gathered suggests that forced displacement in these municipalities may respond to a strategic development logic where criminal violence operates for ends that transcend it and are geopolitical in nature.